Population Pharmacokinetics Modeling of Unbound Efavirenz, Atazanavir, and Ritonavir in HIV‐Infected Subjects With Aging Biomarkers - Dumond, JB (CPT Pharmacometrics Syst Pharmacol, 2016)
Unbound drug is the pharmacodynamically relevant concentration. This study aimed to determine if chronologic age or markers of biologic aging, such as the frailty phenotype and p16(INK4a) gene expression, altered unbound pharmacokinetics (PKs) of efavirenz (EFV) and atazanavir/ritonavir (ATV/RTV). Sixty human immunodeficiency virus (HIV)‐infected participants receiving EFV and 31 receiving ATV/RTV provided 1 to 11 samples to quantify total and unbound plasma concentrations. Population PK models with total and unbound concentrations simultaneously described are developed for each drug. The unbound fractions for EFV, ATV, and RTV are 0.65%, 5.67%, and 0.63%, respectively. Covariate analysis suggests RTV unbound PK is sensitive to body size; unbound fraction of RTV is 34% lower with body mass index (BMI) above 30 kg/m(2). No alterations in drug clearance or unbound fraction with age, frailty, or p16(INK4a) expression were observed. Assessing functional and physiologic aging markers to inform potential PK changes is necessary to determine if drug/dosing changes are warranted in the aging population.